2011
DOI: 10.1140/epjc/s10052-011-1641-2
|View full text |Cite
|
Sign up to set email alerts
|

Texture zeros for the Standard Model quark mass matrices

Abstract: A way of counting free parameters in the quark mass matrices of the standard model, including the constraints coming from weak basis transformations, is presented; this allow to understand the exact physical meaning of the parallel and non-parallel texture zeros which appear in some "ansätz" of the 3 × 3 quark mass matrices, including the CP violation phenomena in the analysis, it is shown why the six texture zeros are ruled out. Finally, a five texture zeros "ansätze"which properly copes with all experimental… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…This pattern was studied previously in Ref. [18]. The complex Hermitian quark mass matrices for this pattern can be written as:…”
Section: Pattern Imentioning
confidence: 96%
See 1 more Smart Citation
“…This pattern was studied previously in Ref. [18]. The complex Hermitian quark mass matrices for this pattern can be written as:…”
Section: Pattern Imentioning
confidence: 96%
“…As it has been shown in several places, the parallel and non-parallel six texture zeros does not work properly and it has been ruled out by analytic [18] and numeric [19] studies (only a charm quark mass half of its measured value can rescue this "anzätze").…”
Section: Five Texture Zerosmentioning
confidence: 99%
“…Interesting alternatives do exist. See, for example, the recent work in [31] where it is shown that having M u similar to Eq. (B1) and an M d given by…”
Section: Appendix B: Yukawa Texturesmentioning
confidence: 99%
“…In particular, it was observed [37][38][39][40] that all texture six zero hierarchical quark mass matrices were ruled out at the level of 3σ, which is a settled and uncontested result. Some predictive texture five zero structures were discussed in [13] which were subsequently ruled out in [38,41,42] on hierarchy and sin2β considerations.…”
Section: Introductionmentioning
confidence: 99%